Research about the most adequate forms of remembering the past and ways of establishing trust in the former Yugoslavia - Petrović Nikola M. (Temida, 2010)
The results of three action studies conducted by the Victimiology Society of Serbia with the aim to raise awareness of Serbian citizens about truth and reconciliation, as well as to examine the attitudes of citizens about the best forms of remembering the past and ways of establishing trust between the different political and ideological groups in Serbia and between the citizens of the member states of the former Yugoslavia, will be presented in this paper. The research was carried out in the period 2002-2010. The first analysis was done on the questionnaires gathered in the period 2002-2004, the second for the period 2004-2009 and the third research was conducted in 2010. A total of 325 filled questionnaires were collected and 3031 informational brochures were handed out. Awareness of the citizens about this issue was raised, and a large number of useful suggestions about the best forms of remembering the past and ways of regaining trust were gathered.